A bibliometric based analysis to identify promising domains of decarbonisation technologies - Costa, P. M.; Tome, P.; Almeida, B.; Bento, N. (2022 7th International Conference on Smart and Sustainable Technologies (SpliTech), 2022)
The high volume of research outputs related to technologies and strategies for decarbonisation can make it challenging to understand the relevance of the presented proposals. In this paper, a bibliometric-based analysis is proposed to understand better the domains and subdomains of decarbonisation technologies that have given more attention by the scientific community. The results show that carbon capture technologies, renewable energy sources, electric mobility, green hydrogen, and storage systems are the technology innovations that have received the most attention in the period 2013 to 2021. These results confirm the traditional supply-side orientation of research on technology innovations.